Data Science 9th International Conference of Pioneering Computer Scientists, Engineers and Educators, ICPCSEE 2023, Harbin, China, September 22-24, 2023, Proceedings, Part II - Yu, Zhiwen; Han, Qilong; Wang, Hongzhi; Guo, Bin.; Zhou, Xiaokang; Song, Xianhua; Lu, Zeguang (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This two-volume set (CCIS 1879 and 1880) constitutes the refereed proceedings of the 9th International Conference of Pioneering Computer Scientists, Engineers and Educators, ICPCSEE 2023 held in Harbin, China, during September 22-24, 2023. The 52 full papers and 14 short papers presented in these two volumes were carefully reviewed and selected from 244 submissions. The papers are organized in the following topical sections: Part I: Applications of Data Science, Big Data Management and Applications, Big Data Mining and Knowledge Management, Data Visualization, Data-driven Security, Infrastructure for Data Science, Machine Learning for Data Science and Multimedia Data Management and Analysis. Part II: Data-driven Healthcare, Data-driven Smart City/Planet, Social Media and Recommendation Systems and Education using big data, intelligent computing or data mining, etc.
Data-driven Healthcare -- Better Fibre Orientation Estimation with Single-Shell Diffusion MRI using Spherical U-Net -- A Method for Extracting Electronic Medical Record Entities by Fusing Multichannel Self-attention Mechanism with Location Relationship Features -- Application of Neural Networks in Early Warning Systems for Coronary Heart Disease -- Research on Delivery Order Scheduling and Delivery Algorithms -- Research on Gesture Recognition Based on Multialgorithm Fusion -- Design of Fitness Movement Detection and Counting System based on MediaPipe -- Data-driven Smart City/Planet -- MetaCity: An Edge Emulator with the Feature of Realistic Geospatial Support for Urban Computing -- Multifunctional Sitting Posture Detector based on Face Tracking -- Real-Time Analysis and Prediction System for Rail Transit Passenger Flow Based on Deep Learning -- Research on Driver Monitoring Systems Based on Vital Signsand Behavior Detection -- People Flow Monitoring based on Deep Learning -- Research on the Influencing Factors of Passenger Traffic at Sanya Airport Based on Gray Correlation Theory -- Qinghai Embroidery Classification System and Intelligent Classification Research -- A Machine Learning-based Botnet Malicious Domain Detection Technique for New Business -- GPDCCL $1!+: (BCross-Domain Named Entity Recognition with Span-Based Domain Confusion Contrastive Learning -- Data Analyses and Parallel Optimization of the Regional Marine Ecological Model -- Comparison of Two Grey Models' Applicability to the Prediction of Passenger Flow in Sanya Airport -- Research on High Precision Autonomous Navigation of Shared Balancing Vehicles Based on EKF-SLAM -- Social Media and Recommendation Systems -- Link Prediction Based on the Relational Path Inference of Triangular Structures -- Research on Link Prediction Algorithms based on Multichannel Structure Modelling -- Modal Interactive Feature Encoder for Multimodal Sentiment Analysis -- Type-Augmented Link Prediction Based on Bayesian Formula -- Multitask Graph Neural Network for Knowledge Graph Link Prediction -- A Short Text Classification Model Based on Chinese Part-of-Speech Information and Mutual Learning -- The Analysis of Phase Synchronisation in the Uniform Scale-free Hypernetwork -- LGHAE: Local and Global Hyper-relation Aggregation Embedding for Link Prediction -- Efficient s-Core Community Search on Attributed Graphs -- Education using big data, intelligent computing or data mining, etc -- A Study on English Classroom Learning Anxiety of Private Vocational College Students -- Research on the Construction of a Data Warehouse Model for College Student Performance -- Research and Application of AI-enabled Education -- A Study on the Online Teaching Input of Higher Education Teachers Based on KMeans Analysis -- Research and Exploration on Innovation and Entrepreneurship Practice Education System for Railway Transportation Specialists.s
Keywords: Data mining; Application software; Machine learning; Education -- Data processing; Social sciences -- Data processing; Data Mining and Knowledge Discovery; Computer and Information Systems Applications; Machine Learning; Computers and Education; Computer Application in Social and Behavioral Sciences